2018
DOI: 10.1159/000492012
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of RASSF1A in Colon Cancer by Suppression of Angiogenesis Signaling and Akt Activation

Abstract: Background/Aims: Silencing of tumor suppressor genes (TSGs) and promotion of angiogenesis are associated with tumor development and metastasis. However, little is known if angiogenic molecules directly control TSGs and vice versa. Methods: A regulatory link between angiogenesis and down regulation of TSGs was evaluated using an anti-cancer agent, andrographolide (AGP) in cancer cells, mouse xenograft tissues and patient derived organoids through gene/protein expression, gene silencing, and immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Our recent findings demonstrate a relationship between angiogenesis signaling and RASSF1A expression which is supported by exogenous VEGF suppression of RASSF1A expression in plant-derived diterpene lactone, andrographolide (AGP) treated metastatic colon cancer cells [25]. To investigate the effect of exogenous VEGF 165 on colon cancer cell metabolism, we stimulated T84 and Colo 205 with different concentration of VEGF 165 as indicated (6 h, 24 h, and 48 h).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent findings demonstrate a relationship between angiogenesis signaling and RASSF1A expression which is supported by exogenous VEGF suppression of RASSF1A expression in plant-derived diterpene lactone, andrographolide (AGP) treated metastatic colon cancer cells [25]. To investigate the effect of exogenous VEGF 165 on colon cancer cell metabolism, we stimulated T84 and Colo 205 with different concentration of VEGF 165 as indicated (6 h, 24 h, and 48 h).…”
Section: Resultsmentioning
confidence: 99%
“…An imbalance of activation of cellular oncogenes such as FoxM1 and loss of function of tumor suppressor genes such as RASSF1A promotes colon cancer progression [25]. We next evaluated RASSF1A and FoxM1 expression in paired colon tumor (CT) and normal tissue (NT) obtained from patient surgical samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated that andrographolide suppressed angiogenic signaling and Akt activation and a recent publication reported that melatonin inhibits VEGF (aggravates edema and the extravasation of the immune cells from blood vessels) expression in vascular endothelial cells [32,83]. In the ICU, deep sedation is associated with increased long-term mortality, and the application of melatonin reduces sedation use and the frequency of pain, agitation, and anxiety.…”
Section: Present and Future Treatment Aspects Of Corona Virusmentioning
confidence: 99%
“…Currently, researchers are not very knowledgeable about the complex pathogenesis of MDS. However, angiogenesis has been regarded as a vital pathophysiological process in solid tumors for tumor growth, proliferation, and metastasis . In addition, recent studies showed that angiogenesis and angiogenesis factors play a vital role in the onset and development of MDS and AML .…”
Section: Introductionmentioning
confidence: 99%